Ózbek hám qaraqalpaq til biliminde frazeologiyalıq sistemasınıń izertleniw tariyxı (SCIENCE and SOCIETY, 2024)
The article deals with the history of the study of phraseological units in Uzbek and Karakalpak linguistics. It also pro- vides information about the study of phraseological units divided into periods and the current comparative study process.